“Like Pieces in a Puzzle”: Online Sacred Harp Singing During the COVID-19 Pandemic - Morgan-Ellis, Esther M. (Frontiers in Psychology, 2021)
Sacred Harp singers the world over gather weekly to sing out of The Sacred Harp, a collection of shape-note songs first published in 1844. Their tradition is highly ritualized, and it plays an important role in the lives of many participants. Following the implementation of lockdown protocols to combat the COVID-19 pandemic, groups of Sacred Harp singers quickly and independently devised a variety of means by which to sing together online using Zoom (“zinging”), Jamulus (“jamzinging”), and Facebook Live (“stringing”). The rapidity and creativity with which Sacred Harp singers developed ways to sustain their activities attests to the strength and significance of this community of practice, and in this article I describe each modality and provide an account of how it came to be developed and widely used. As a participant-observer, I completed extensive fieldwork across these digital sites and conducted semi-structured interviews with twenty-two other singers. I found that online singing practices have reshaped the Sacred Harp community. Many singers who did not previously have the opportunity to participate now have access, while others have lost access due to technological barriers or lack of interest in online activities. At the same time, geographical barriers have disintegrated, and singing organizers must make an effort to maintain local identity. A stable community of singers has emerged in the digital realm, but it is by no means identical to the community that predated the pandemic. I also identify the ways in which online singing has proven meaningful to participants by providing continuity in their personal and communal practice. Specifically, online singing allows participants to access and celebrate their collective memories of the Sacred Harp community, carry out significant rituals, and continue to grow as singers. While no single modality replicates the complete Sacred Harp singing experience, together they function “like pieces in a puzzle” (as one singer put it), allowing individual participants to access many of the elements of Sacred Harp singing that are most meaningful to them.